(NsINTEZ SISTEM S OBRATNOJ SWQZX@ (B:s (NpER(B. (NS ANGL(B. /s - (NgOROWIC(B, (NaJZEK m(B.s; (NgAJSINSKIJ(B, (Na(B.(Nn(B.s; (NmEEROW(B, (Nm(B.(Nw(B.s ((NmOSKWA (B:s (NsOW(B. (NRADIO(B,s, 1970)
(NbIBLIOGR(B.: (NS(B. 586 - 590 (141 (NNAZW(B.)s
(NpREDM(B. (NUKAZATELX(B: (NS(B. 591 - 594s
Keywords: (NaWTOMATI^ESKIE SISTEMY UPRAWLENIQs; (NoBRATNAQ SWQZXs